3D beam–column corner joints retrofitted with X-shaped FRP sheets attached via the EBROG technique. (15th March 2019) - Mostofinejad, Davood; Hajrasouliha, Mohammadjavad
Highlights: Six half-scale 3D RC beam-column joint specimens were retrofitted with FRP sheets. X-shaped FRP sheets were used with the EBROG technique. The proposed strengthening pattern prevented the joint shear failure. The plastic hinge was relocated away from the column interface into the beam. Abstract: Beam-column joints are fundamental structural components of a stable structure. Corner joints are more likely to fail due to their small size and inferior confinement. This calls for three-dimensional (3D) strengthening of corner joints with fiber reinforced polymer (FRP) sheets to improve the load carrying capacity and ductility of beam–column connections. The present study investigates the shear strength of non-seismic 3D corner joints lacking adequate transverse reinforcement in their joint panel but strengthened with carbon fiber reinforced polymer (CFRP) sheets. The externally bonded reinforcement on groove (EBROG) technique is used in the joints to delay the debonding of CFRP sheets off the concrete substrate. Maximum expected moment resistance of a beam/connection is typically obtained at the column interface. This, therefore, requires sufficient bonding strength provisioned between the FRP sheet and the concrete substrate over an acceptable range of the bonding length. Practical limitations, however, do not allow for enough length of the column interface to be strengthened. A new anchorage system of FRP fans is, therefore, provisioned to attain the required bonding strength. The results are verified by studying the hysteretic response of the 3D corner joints strengthened via the proposed EBROG method and with the provisioned FRP fans. For this purpose, six half-scale 3D joint specimens were constructed and subjected to relevant tests. The specimens included a control, one reference specimen that satisfied the current building codes, and four FRP-retrofitted specimens with X-shaped strengthening patterns. The results revealed that the proposed strengthening pattern prevented joint shear failure. Furthermore, the proposed EBROG technique outperformed the externally bonded reinforcement (EBR) techniques as evidenced by the higher values of maximum load-carrying capacity and ductility recorded by the joint while CFRP debonding off the concrete substrate was also delayed. Maximum loading led to a drift ratio of 4.5%, indicating that application of the EBROG technique combined with FRP fans inhibited load reductions throughout the test period.